Breaking through the glass ceiling: meritocracy steps for women's civil service careers - Suryani, Anamira; Rossanti, Niluh Putu Evvy; Adda, Harnida Wahyuni (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
This study investigates the challenges posed by the glass ceiling and the implementation of meritocracy for female civil servants (in Palu City, aiming to identify strategies for enhancing career progression. Employing a constructivist research paradigm with a qualitative approach, data were gathered through interviews including the Mayor, City Secretary, BKPSDMD Head, and representatives from various departments within the Palu City Government. Analysis was conducted using triangulation techniques aided by NVIVO 14 software. Findings reveal that the glass ceiling manifests as conflicts in work-life balance, limited decision-making authority, and entrenched gender biases, hindering women's career advancements. Nonetheless, it also serves as motivation for female civil servants to assertively engage in career development. Overcoming these obstacles demands exceptional resilience, perseverance, and a composed demeanor in facing challenges. The glass ceiling can stimulate proactive measures toward career success among women. Conversely, a fair and transparent meritocracy system emerges as a viable solution to mitigate the glass ceiling's effects. This entails implementing mentoring, coaching, training, and educational initiatives addressing women-specific workplace challenges such as time management, salary negotiations, and work-life equilibrium.